Analysis of phytochemical constituents using GC–MS, evaluation of antioxidants and antibacterial activities of Maerua oblongifolia root bark extracts - Mamo Dikamu; Dessie Ezez; Habtamu Birhanu; Aweke Mamo; Molla Tefera (Discover Applied Sciences)
Abstract Medicinal plants contain a variety of bioactive compounds that provide antioxidants and antibacterial activities, which can be used to improve novel antibiotics. Therefore, this study was aimed to investigate phytochemical constituents, antioxidant activities, and antibacterial activities in Maerua oblongifolia root bark extracts. Different solvent extracts revealed that the total phenolics, flavonoids and tannins contents were varied in the range from 10.611–20.947 mg GAE/g, 0.776–15.739 mg CE/g and 1.382–2.328 mg TAE/g respectively. The antioxidant activities in terms of percentage inhibition effects were arranged in the order: acetone (95.4%) > ethanol (93.66%) > ethyl acetate (83.75%) > dichloromethane (78.31%) for 2, 2-diphenyl -1- Picryl Hydrazyl (DPPH), and ethanol (96.24%) > acetone (92.83%) > ethyl acetate (87.95%) > dichloromethane (85.13%) for ferric reducing antioxidant power (FRAP). The major biologically active compounds found in M. oblongifolia root bark were $$γ$$ γ -sitosterol (19.65%), Stigmasterol (19.38%), 4-ethenyl-2, 6-dimethoxy phenol (4.12%), 2-(Benzylmethylamino) ethanol N-oxide (4.04%), Butyl butanoate (3.05%), Methyl salicylate (2.71%), Di-isobutyl Phthalate (1.79%), and 1-(10,10-Dimethyl-3,3-dioxo-3-thia-4-azatricyclo[5.2.1.0 (1,5)]dec-4-yl)-3-methylpent-4-en-1-one (1.62%). M. oblongifolia root bark extracts demonstrate antibacterial activities against the tested bacterial strains. Acetone and ethanol extract of Staphylococcus aureus displayed very potent antibacterial activity against the bacterial activities in nutrient agar with inhibition zone of 33.24 mm and 23.57 mm respectively. Ethyl acetate with inhibition zone (8.12 mm) in nutrient agar for Escherichia coli and acetone with inhibition zone (9.65 mm) in Muller-Hinton agar for Staphylococcus aureus exhibited the minimum inhibitory effects. The results of principal component analysis (PCA) showed two principal components. The PC1 exhibited a significant positive correlation with phenol, DPPH, and FRAP while PC2 was characterized by flavonoid and tennis. The results revealed that phenolics and flavonoids were strongly correlated with DPPH and FRAP. This study provides the scientific evidence on the biologically active phytochemical constituents of M. oblongifolia root bark extracts.